2007
DOI: 10.1074/jbc.m703075200
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Effects of Selenium Are Mediated through 15-Deoxy-Δ12,14-prostaglandin J2 in Macrophages

Abstract: Selenium is an essential micronutrient that suppresses the redox-sensitive transcription factor NF-B-dependent proinflammatory gene expression. To understand the molecular mechanisms underlying the anti-inflammatory property of selenium, we examined the activity of a key kinase of the NF-B cascade, IB-kinase ␤ (IKK␤) subunit, as a function of cellular selenium status in murine primary bone marrow-derived macrophages and RAW264.7 macrophage-like cell line. In vitro kinase assays revealed that selenium supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
148
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(163 citation statements)
references
References 43 publications
8
148
0
5
Order By: Relevance
“…Moreover, characterization of the recently developed SelK knockout mouse model demonstrated that SelK deficiency leads to deficient Ca 2ϩ flux during immune cell activation and impaired immune response (358). These findings suggest that SelK and SelS might mediate the anti-inflammatory effects of Se and its role in the immune system (265,361). However, the molecular mechanisms by which SelS and SelK affect immune function and inflammatory response await further investigation.…”
Section: Selenoproteins K and Smentioning
confidence: 99%
“…Moreover, characterization of the recently developed SelK knockout mouse model demonstrated that SelK deficiency leads to deficient Ca 2ϩ flux during immune cell activation and impaired immune response (358). These findings suggest that SelK and SelS might mediate the anti-inflammatory effects of Se and its role in the immune system (265,361). However, the molecular mechanisms by which SelS and SelK affect immune function and inflammatory response await further investigation.…”
Section: Selenoproteins K and Smentioning
confidence: 99%
“…However, elegant experiments involving mouse bone marrow-derived macrophages (BMDM) and RAW 264.7 mouse macrophages revealed an important, albeit complex effect of altered cellular Se status and NFjB activation. In these studies, BMDM were isolated from mice fed Se-deficient and Se-supplemented diets containing 0.01 or 0.4 ppm Se as described (174,259). BMDM and RAW 264.7 cells were cultured in media containing 5% defined FBS with total Se of 6.0 nM (low Se) or the same media supplemented with 2 lM Se (high Se).…”
Section: Se and Eicosinoid Synthesis In Macrophagesmentioning
confidence: 99%
“…-GPxs can modulate the production of biologically active eicosanoids by the COX and LOX pathways [74]. -Se down-regulates the expression of inflammatory genes [75].…”
Section: Seleniummentioning
confidence: 99%